It's Tee Time: An Ultrabroadband Componentless Bias Tee: A Planar Ultrabroadband Componentless Bias Tee in Microstrip Line Technology - Kögel, Tobias; Scheder, André; Meyl, Markus; Sohr, Stefan; Vossiek, Martin (IEEE Microwave Magazine, 2024)
With the trend toward ever-higher frequencies and continuously increasing bandwidth in communication for 5G and 6G as well as in the radar domain, the demand on broadband hardware components is rising accordingly [1]. Circuits that were initially considered simple have to be optimized further in order to meet challenging demands.
CRIS-Team Scopus Importer:2024-05-24